Beseda kot teologija - Matjaž, Maksimilijan (Bogoslovni vestnik, 2013)
The paper first gives a consideration of the word - logos and of the responsibility of academic institutions for maintaining the word as a basic human actuality in the society. Every genuine word committed to truth and coming from the man's very core is always a novelty and as such a reflection of the absolute Word. The second part presents the circumstances of how the Constitution on Divine Revelation of the Second Vatican Council came into being. Thereby the Council put the Bible and, consequently, the word again into the centre of theology and presented it as the rule of faith and the spring of life. The process delineated by this documents is still a topical vision and a dynamic force to renew theological hermeneutics and the happenings in Church and in society in general.
Keywords: sveto pismo; beseda; Bible; word; logos; biblical hermeneutics; biblična hermenevtika; drugi vatikanski koncil; Second Vatical Council